Mechanisms of aneuploidy and its suppression by tumour suppressor proteins (Swiss Medical Weekly, 2011)
Aneuploidy, as a result of numerical changes in chromosome number, was observed in tumours almost a century ago. The molecular mechanisms underlying this phenomenon and their impact on tumour development are still poorly understood. A series of recent observations provide direct linkages between the normal function of tumour suppressor proteins and the suppression of aneuploidy. The prospects that these findings offer for understanding the role of aneuploidy in cancer are discussed in this review.